The Effect of Tax Awareness, Tax Sanctions, and Tax Literacy on Tax Compliance (Case Study on Taxpayers Registered at the Kediri City Pratama Tax Service Office (KPP) - Sabaha, Syekha Nur; Permatasari, Intan Kurnia (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of tax awareness, tax sanctions, and tax literacy on the tax compliance of Taxpayers registered at the Kediri City Primary Tax Service Office. This research method uses a quantitative approach with primary data obtained through a questionnaire with a Like Scale of 1 – 5. The population in the study was all people of Kediri City. The sample used in this study were taxpayers registered at the Kediri City Primary Tax Service Office with a sampling technique using non-probability sampling. The number of samples used in this study was 140 respondents. Data analysis was carried out using the Statistical Product and Service Solution (SPSS) method. The result of the study indicates that tax awareness and tax literacy affect taxpayer compliance.